Fragile Avatars: Playful Betrayal in Children's Online Hacking Practices. - Helgesen, Espen (Ethnos: Journal of Anthropology, 2019)
As children in Norway increasingly spend time in online worlds, often identifying closely with their avatars, the potential for experiencing distress as a consequence of losing control of these digital selves has also increased. This article investigates the local notion of 'hacking' among a group of 8- and 9-year-old friends, and shows how users of the online world MovieStarPlanet must be attuned to the always imminent threat of having their avatars seized by other users. Expanding on Gregory Bateson's concept of framing to illuminate the paradoxical nature of online play, the article argues that hacking practices involve the simultaneous conjuring of apparently contradictory frames. Taking advantage of the fluid boundaries between play and non-play, the children made subversive use of egalitarian values of inclusion to exploit the trust of their friends, allowing them to mute and exclude other users.